Supply Chain Operation Reference Analysis for the Village Superior Product E-Commerce of BUMDes - Sunaryono Sunaryono; Rizaldy Rizaldy; Zulimi Zulimi (Research Synergy Press, 2022)
This research aims to determine the Chain of sales of Village featured -products. In Addition, it can cut off the Chain of sales from farmers to consumers. In contrast, the scope of this study discusses the village product selling by BUMDes only. This study type is descriptive qualitative with the qualitative descriptive concept—its concept of research with obtaining potluck data. To ensure the availability of material supply, the method for is SCOR analysis. Analyze the supply chain of village products commercial with the methods of Supply Chain Operation Reference (SCOR). SCOR is maintained and developed by a nonprofit organization called the Supply Chain Council (SCC). The model is a reference model utilized to map benchmarks and improve supply chain operations. The research results showed bumdesmart has an effective cutting the Chain of sales. So from the results of this research provide a positive impact for farmers. In conclusion, bumdesmart design to cut the Chain of sale of village products through BUMDes. With the results as direct intermediaries and liaisons between farmers and consumers.